Song Gölü Havzası'nın (Kırgız Cumhuriyeti) fiziki coğrafya özellikleri - Özer, Özgür (My University, 2023)
“Song Gölü Havzasının (Kırgız Cumhuriyeti) Fiziki Coğrafya Özellikleri” isimli bu çalışmada adı geçen sahanın fiziki coğrafya özelliklerinin saptanması amaçlanmıştır. Bu kapsamda arazi çalışmaları, geziler ve literatür çalışmaları yapılarak Kırgız Cumhuriyeti sınırları içerisinde yer alan havzanın jeoloji, jeomorfoloji, iklim, toprak, bitki ve hidrografik özellikleri belirlenmiştir. Buzul ve su kaynakları bakımından zengin olan Kırgız Cumhuriyetinde 3.000’den fazla göl bulunmaktadır. Havzası Orta Tanrı Dağları ile Kuzey Tanrı Dağlarının bağlantı noktası üzerinde yer alan Song Gölü, ülkenin Issık Göl’den sonra en büyük ikinci gölü ve en büyük tatlı su kütlesidir. Jeolojik bulgular dağların güneyinde kalan havzanın Hersinyen kıvrılmasında çöktüğü, Senozoik boyunca dış kuvvetler yardımıyla Song Gölü Dağlarının zirvelerinden sediment kopartarak tabana biriktirdiği ve postglasyal dönemde eriyen buzulların sularının gölü oluşturduğunu göstermektedir. Bir dağ gölü olan Song’un ortalama deniz seviyesinden yüksekliği 3.016 metredir. Birçok göçmen kuş için kısa süreli konaklama sahası ve çeşitli su ve bataklık kuşları için yaşam alanı olan gölün özellikle kuzey kıyıları kamp turizmi ve hayvancılık bakımından önemlidir. Göl etrafında yerleşim yeri olmamasına rağmen yaz aylarında Kırgız Cumhuriyetinin Koçkor, Narın ve Atbaşı gibi yörelerinden getirilen hayvan sürüleri havzadaki gür otlaklarda otlatılmaktadır. Yaklaşık yirmi küçük dereden ve buzullardan beslenen göle en yakın kalıcı yerleşim, Narın Vilayetinin Cumgal Rayonunda yer alan ve nüfusu 7.009 kişi ve rakımı 1.653 m. olan Çayek’tir. Çayek’in Son Gölü’ne olan mesafesi 38 km.’dir. Ayrıca son dönemde yapılan çalışmalar ile gölün balık faunası artırılmaya çalışılmaktadır. Song Gölü Irmağı veya Kökcerti vasıtası ile Narın Irmağına su çıkışı olan Song Gölünün havzası, Siriderya havzasının alt havzası olan ve Özbekistan ve Kırgızistan’da yer alan Narın havzasının bir alt havzasıdır. Havza, Song Gölü’nün güneyinde yer alan Moldo Dağları ile Narın havzasının ana bölümünden; gölün kuzeyinde kalan Song Göl Dağları ile Cumgal Vadisinden ve kuzeydoğusunda bulunan ve yüksekliği 2.664 metre olan Kızart geçidi ile Koçkor havzasından ayırmaktadır. Song Gölü havzası alanı yaklaşık 278 km2 ’lik alanından iki kat daha fazladır. Kırgızistan coğrafyasına ilişkin olarak Türkiye Türkçesinde yapılmış çalışmalara bakıldığında, genellikle beşeri coğrafya alanlarına odaklanıldığı, ülkenin fiziki coğrafyasına odaklı yeterince Türkçe çalışma olmadığı görülmektedir. Kırgız Cumhuriyeti dünyada herhangi bir açık denize uzaklığı en fazla olan dolayısıyla dünyanın en karasal ülkesidir. Ortalama yükseltisi 2.750 metre olan ülkenin arazisinin yüzde 90’ı engebelidir. Bu sayede farklılaşan peyzajlar, bitki örtüsü ve hayvan çeşitliliği sağlamaktadır. Dolayısıyla çalışma, dünyanın en dağlık birkaç ülkesinden birisi olan Kırgız Cumhuriyetinin fiziki coğrafya özelliklerini tespit edilmesi bakımından da önemlidir.

The aim of this study was to determine the physical geography characteristics of the basin of Song Kol Lake. In this framework, geological, geomorphological, climatic, soil, plant, and hydrographic characteristics will be determined. Kyrgyz Republic which is a rich country for glacier and water has more than 3,000 lakes. Song Kol with its basin located at the junction zone between the North Tien Shan and Middle Tien Shan in Central Kyrgyzstan as is the second largest lake and the largest fresh water body of the country. Altitude of Song is 3,016 meters as a mountain lake. Especially, the North coasts of the lake which is a stop-over point of migratory birds as well as biotope of numerous water birds and swamp birds has an importance for camping tourism and husbandary. Although no settlement is present around the lake, herds from Kyrgyzstan’s districts such as Kochkor, Naryn, and Atbashy are grazed in lush grasslands of the basin. The nearest settlement to the lake fed by about twenty streams and glaciers is Chaek located in Jumghal District of Naryn Province with a population of 7009. Furthermore, fish fauna of the lake were enriched by the recent projects. The basin of Song Kul with an outflow to Naryn River is a sub-basin of Naryn basin located in Uzbekistan and Kyrgyzstan as a sub-basin of Syr Darya basin. The basin is separated from main Naryn basin by Moldo Mountains located in the South of the lake, Jumghal valley by Song Kol Mountains located in the North of the lake and Kochkor by Kyzart Pass with an altitude of 2,664 meters in the northeast of the lake. The lake occupies a basin of approximately two-fold lake of 280 km2. Taking the geographical studies on Kyrgyzstan carried out in Turkish, researchers have focused on human geography. Kyrgyzstan is the most continental country in the world as the farthest country to any ocean. About 91% of the country with a mean altitude of 2,750 meters is mountainous. Hence, various landscapes present a large biodiversity. As a conslusion, the present study has of importance with respect to determining physical geography characteristics of Kyrgyzstan.
The physical geography characteristics of the Basin of Song Kul Lake
Keywords: . Taking the; 000 lakes; 016 meters as a mountain lake; 664 meters in the northeast of the lake; 750; About 91% of the country with a mean altitude of 2; Although no settlement is present around the lake; Altitude of Song is 3; and Atbashy are grazed in lush grasslands of the; and hydrographic characteristics will be determined; As a; basin; basin is separated from main Naryn basin by Moldo Mountains located in the South of; basin located at the junction zone between the North Tien Shan and Middle Tien Shan; basin located in Uzbekistan and Kyrgyzstan as a sub-basin of Syr Darya basin; Biyoçeşitlilik; Chaek located in Jumghal District of Naryn Province with a population of 7009; climatic; coasts of the lake which is a stop-over point of migratory birds as well as biotope of; conslusion; districts such as Kochkor; Especially; farthest country to any ocean; fish fauna of the lake were enriched by the recent projects; Fiziki coğrafya; Furthermore; geographical studies on Kyrgyzstan carried out in Turkish; geological; geomorphological; Hence; herds from Kyrgyzstan’s; human geography; husbandary; In this framework; in Central Kyrgyzstan as is the second largest lake and the largest fresh water body of; is a rich country for glacier and water has more than 3; Jumghal valley by Song Kol Mountains located in the North of the lake and; Kırgızistan; Kochkor by Kyzart Pass with an altitude of 2; Kyrgyz Republic which; Kyrgyzstan; Kyrgyzstan is the most continental country in the world as the; meters is mountainous; Narın; Naryn; numerous water birds and swamp birds has an importance for camping tourism and; Physical geography; plant; researchers have focused on; soil; Song Gölü; Song Gölü (Kırgızistan); Song Gölü (Kyrgyzstan); Song Kol with its; Tanrı Dağları; The; The aim of this study was to determine the physical geography characteristics of; the basin of Song Kol Lake; The basin of Song Kul with an outflow to Naryn River is a sub-basin of Naryn; the country; the lake; The lake occupies a basin of approximately two-fold lake of 280 km2; The nearest settlement to the lake fed by about twenty streams and glaciers is; the North; the present study has of importance with respect to determining physical geography characteristics of Kyrgyzstan; various landscapes present a large biodiversity